Analisis Representasi dan Budaya Visual Logo Haus! Terhadap Brand Attractiveness di Kalangan Anak Muda - Vivi Varlina; Chintya Maulini (GESTALT : JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
A logo is a key element in forming visual perceptions that form a brand image. This research examines Logo Haus as a new brand, which has succeeded in attracting the attention of young people. This study uses a descriptive qualitative approach that connects visual elements through Gestalt analysis and cultural studies. The research results found that the use of the Gestalt visual representation of the Haus! can create a cohesive and attractive impression. An in-depth analysis of the visual representation of this logo also provides insight into how logo design influences brand appeal in the context of popular culture and youth trends. The use of a combination of picture mark and letter mark logo type through the choice of colors and neat element representation, helps shape the Haus! Indonesia is connected to popular culture and is of interest to the younger generation.